Antibacterial potency of simple fractions of ethyl acetate extract of Begonia baliensis - HARTUTININGSIH-M. SIREGAR; R. S. PURWANTORO; PRAPTIWI PRAPTIWI; A. AGUSTA (Nusantara Bioscience, 2018)
Siregar HM, Purwantoro RS, Praptiwi, Agusta A. 2018. Antibacterial potency of simple fractions of ethyl acetate extract of Begonia baliensis. Nusantara Bioscience 10: 159-163. Balinese people utilized Begonia baliensis Girm. (Begoniaceae) as traditional medicine to relieve cough. It was applied in a unique way by inserting the plant material into a bamboo column and then burning it in the fire. The liquid produced by the combustion process was used as a cough medicine. Based on this traditional knowledge, it is expected that B. Baliensis has antibacterial activity. B. baliensis plant collected from Bukit Sangyang, Penebel, Tabanan-Bali has been used in this study. The chemical compounds of ethyl acetate extracts were isolated/ separated by column chromatography. The obtained fractions were analyzed for antibacterial activity by disc diffusion assay against Escherichia coli, Bacillus subtilis, Staphylococcus epidermidis and Staphylococcus aureus. Chromatographic column yielded 14 simple fractions, whereas antibacterial test results showed 5 active fractions. Fraction 3 (F3) was active against S. epidermidis, fraction 5 (F5) against E. coli and S. epidermidis, while fractions 10, 11 and 12 were active only against Bacillus subtilis. Isolation and purification of the active components likely increased their potential as antibacterials.